Enough - Winkler, Irwin; Cowan, Rob; Apted, Michel ([Culver City, Ca.] : Columbia Pictures Industries, 2002)
Slim thought she was entering a life of domestic bliss when she married the man of her dreams. After the arrival of her daughter, Slim begins to see the hidden, abusive side of her husband. Terrified for her and her daughter's safety, Slim flees. But her husband's resources allow him to relentlessly pursue them. Finally Slim fights back, engaging her husband in a physical and psychological battle
Executive producer, E. Bennett Walsh ; writer, Nicholas Kazan ; editor, Rick Shaine
Cast: Jennifer Lopez, Billy Campbell, Juliette Lewis
VCD format
Keywords: Man-woman relationships in motion pictures; Violence in motion pictures